Arteterapia, a arte de cuidar com arte: um caminho para o humano em sua totalidade - Gaspar, Fabiola Maria (2013)
This Master s dissertation deals with aspects tied to the Human Being, the Arts, Education, Creativity, Health and Spirituality. The theoretical referential is based on authors representing these areas such as Leonardo Boff, Jean Yves Leloup, Rubem Alves, Iuri Reblin, Carl Gustav Jung, Fritjot Capra, Ângela Philippini and Sonia Tommasi. Throughout the research one could perceive that the references of these areas sometimes walk separately and sometimes meet. And that Art Therapy is a therapeutic activity which amalgamates all of these areas with the goal of promoting the return of the whole being in the direction of its sacredness. It has been verified that all creatures have the deepest desire to return to the Creator and that art has been the instrument, from the remotest of times, of communication of the human being with the world around it. Finally, the paper presents various practical activities to show how Art Therapy can be constituted as a valuable tool in opening and consolidating paths which permit the encounter with the totality for an increasing number of people.